Re-signifying and negotiating indigenous identity in university spaces: a qualitative study from Chile. Issue 2 (1st February 2020) - Webb, Andrew; Sepúlveda, Denisse
ABSTRACT: This article draws on life history interviews with Indigenous university students in Chile to demonstrate the ways these young people re-signify and negotiate their participation in higher education. International scholarship has emphasized the unequal conditions for minority groups to access higher education, but attention also needs to be given to the ways students forge new identity pathways for themselves within these racialized environments. Our analysis utilizes LatCrit studies to emphasize how marginal and hybrid identities enable forms of resistance and counter-narratives to dominant (white) ideologies and assimilatory practices. We focus on the concept of community cultural wealth and the empowerment that aspirational and resistant capital can give to Indigenous youth, providing alternative motives for their studies in relation to the Indigenous communities to which they belong. The paper contributes to this scholarship by underscoring positive aspects of Indigenous student resistance and agency from an understudied context in Latin America.